A Longitudinal Study of Hospitality Students' Emotional Intelligence: Comparing High and Low Scores. Issue 2 (3rd April 2017) - Wolfe, Kara L.
ABSTRACT: Emotional intelligence (EI) is the ability to perceive and regulate or use emotions to improve performance. Managers with higher EI are more successful (Langhorn, 2004); therefore, hospitality educators should want to assist students in improving their EI skills. This longitudinal study looks at whether hospitality management students can increase their EI. The research consisted of collecting several years of pretest EI data from hospitality management students in an introductory class, then incorporating EI lessons into the course and administering a posttest. Finally, EI scores were again collected in a capstone course, and the students' EI scores were matched to their earlier scores to track changes. The results show that students with low EI scores in the introductory course significantly improved their EI scores, but those with high EI did not. Recommendations are made for how to incorporate EI into the curriculum.